2004
DOI: 10.1161/01.hyp.0000149249.09147.b4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Podocytes for Reversal of Glomerulosclerosis and Proteinuria in the Aging Kidney After Endothelin Inhibition

Abstract: Abstract-The cause of focal-segmental glomerulosclerosis as a consequence of physiological aging, which is believed to be inexorable, is unknown. This study investigated whether inhibition of endothelin-1, a growth-promoting peptide contributing to renal injury in hypertension and diabetes, affects established glomerulosclerosis and proteinuria in the aged kidney. We also determined the role of endothelin receptors for podocyte injury in vivo and in vitro. Aged Wistar rats, a model of spontaneous age-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 41 publications
10
145
1
Order By: Relevance
“…In a similar vein, the authors observed improved endothelium-mediated vasodilation upon ET A receptor blockade in aged male mice (25). In addition, ET-1 appears to contribute to renal injury in aged male rats, suggesting that the effects of a hyperactive endothelin system extend beyond the vasculature into organs like the kidney (77). The mechanisms stimulating the ET-1 system in aging are not fully understood.…”
Section: Endothelin System In Agingmentioning
confidence: 83%
“…In a similar vein, the authors observed improved endothelium-mediated vasodilation upon ET A receptor blockade in aged male mice (25). In addition, ET-1 appears to contribute to renal injury in aged male rats, suggesting that the effects of a hyperactive endothelin system extend beyond the vasculature into organs like the kidney (77). The mechanisms stimulating the ET-1 system in aging are not fully understood.…”
Section: Endothelin System In Agingmentioning
confidence: 83%
“…Podocytes express a diversity of vasoactive factors and their receptors, including angiotensin II, endothelins, NO. 42,43 We previously reported the reduction of C-type natriuretic peptide receptor in the glomerular podocytes of DSHs. 24 We also demonstrated the modulation of adrenomedullin expression in response to various injurious stimuli in cultured podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…48 -50 In these studies, regression of renal lesions was achieved using targeted pharmacological interventions such as ET-A blockers 49 or angiotensin-converting enzyme inhibitors 48 or by increasing leptin expression and levels, 50 suggesting the involvement of these systems in the mechanisms of renal injury. Our study suggested that in hypercholesterolemia, renal injury may also be prevented or reverted by controlling dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%